The geographically weighted regression approach in analyzing the factors forming economic growth - Rendra Erdkhadifa (Indonesian Journal of Islamic Economics Research, 2019)
East Java has a great position to become one of a province with a predominance of the economic studies which has an allotment of a region with affects culture. Known as the Mataraman based on a culture that is inherited. Derived from the influence of ancient culture Mataram which centered on central java and D.I Yogyakarta. The effect of great culture on Mataraman region is viewed as one characteristic that has the ability on economic activities, with the result that causes differences in economic growth’s indicators as reflection of economic’s prosperity. This study looks at the factor which provide economic growth is based on Mataraman characteristic by Government Expenditure, Gross Domestic Regional Product, Mataraman, Original Local Government Revenue and analyzed using regression and Geographically Weighted Regression to get best model economic growth in Mataraman, East Java. The conclusion of the study is every object has different factor to influence economic growth